Septal defect with polyvalvular involvement: A cardiac imaging hallmark of Trisomy 18 - Usha Nandhini Sennaiyan; SKiruthika; Mani Ram Krishna (Wolters Kluwer Medknow Publications, 2021)
Congenital Heart Diseases occur in close to 90% of children with Trisomy 18. A ventricular septal defect along with abnormalities of more than one cardiac valve is considered to be an imaging hallmark of Trisomy 18. We present echocardiographic images of an infant with Trisomy 18 who had a large ventricular septal defect and abnormalities of all cardiac valves.